Security sector reform : a case study approach to transition and capacity building - Meharg, Sarah Jane.; Arnusch, Aleisha, 1977-; Merrill, Susan; Army War College (U.S.). Strategic Studies Institute; Peacekeeping and Stability Operations Institute (Carlisle, PA : Strategic Studies Institute, U.S. Army War College, 2010)
This paper explores the definition of SSR as it has emerged in the international community. It examines the makeup of the security sector. identifies emergent principles for implementing SSR in the community of practice, and specifies the outcomes that SSR is designed to produce. Supporting case studies of Haiti, Liberia, and Kosovo assess the impact of SSR programs on host nation security sectors. The authors conclude that those conducting SSR programs must understand and continually revisit the policy goals of SSR programs, to develop concepts that support a transitional process that moves forward over time. They also identify a need for rebalancing resources committed to SSR, especially since justice and civil law enforcement typically are undersourced as elements of SSR. Lastly, the authors cite the need for more flexible and better integrated funding processes to support SSR activities within the U.S. Government.
Introduction : a primer to security sector reform -- Security sector reform agendas -- Organization for Economic Cooperation and Development -- European Union -- United Kingdom Government -- U.S. Government -- Principles of security sector reform -- State security actors -- Civilian police -- State justice actors -- Nonstate providers of justice and security -- Private sector providers of safety and security -- Civil society -- Other nonstate actors -- SSR activities -- Obstacles to successful SSR -- Summary -- A note on the case studies -- Kosovo : rule of law, police, and judiciary -- Kosovo backgrounder --- Kosovo timeline -- NATO intervention -- Mitrovica clashes -- Independence plan -- United Nations Interim Mission in Kosovo (UNMIK) 1999 to present -- Security sector reform in Kosovo -- Police -- Department of Justice -- Courts -- Kosovo rule of law -- Summary -- Discussion questions -- Additional references -- Liberia : nonstate security actors -- Liberia backgrounder -- History of international engagement -- Contemporary context -- Progress -- Challenges -- Overview -- Security sector reforms in Liberia -- Nonstate actors challenging SSR in Liberia -- Ex-combatants -- Youth -- Women -- Community-based security actors and mechanisms -- State police : capacity and reach -- Summary -- Discussion questions -- Additional references -- Haiti : police and law enforcement -- Haiti backgrounder -- Political violence -- Corruption -- Criminality -- Environment -- International interventions -- Haiti timeline -- United Nations Stabilization Mission in Haiti (MINUSTAH) -- Security sector reform in Haiti -- Haitian National Police (HNP) -- Challenges to Security sector reform -- Comprehensive strategy for SSR -- Resources -- Public confidence -- Gender -- Haiti policing and law enforcement -- Summary -- Discussion questions -- Additional references.
"January 2010."
Includes bibliographical references.
Also available online in PDF format from Strategic Studies Institute (SSI) web site. Adobe Acrobat Reader required.
Keywords: Security sector; Rule of law; Peace-building -- Haiti; Armed Forces -- Stability operations